PENGGUNAAN DIKSI DALAM NOVEL “PERGI” KARYA TERE LIYE - Syafi’ Junadi; Mariana Mariana (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2020)
Diction is a diction or a choice of words which includes an understanding of which words are used to convey an idea, how to form the right grouping of words or use appropriate expressions, and which style is best used in a situation. The GorysKeraf divides meaning into two types, namely denotation meaning and connotation meaning. Then divide the change of meaning into six types, namely expansion of meaning, narrowing of meaning, amelioration, observation, metaphor and metonymy. There are two formulation of the problem in this study, namely (1) How is the variation of the use of diction in the novel